2020
DOI: 10.1017/s0954579419001706
|View full text |Cite
|
Sign up to set email alerts
|

Mentalizing in mothers and children with type 1 diabetes

Abstract: Studies suggest that the relationship between psychosocial well-being and type 1 diabetes (T1D) is bidirectional, with T1D typically having a negative influence on psychological functioning, which in turn negatively affects the course of T1D. Here, we investigate the potential role of the capacity for mentalizing, or reflective functioning, in children and their mothers in diabetes control. We tested differences in mentalizing as assessed by the Reflective Functioning Scale in two groups of mother–son dyads wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 88 publications
1
14
0
Order By: Relevance
“…According to this, diabetes studies have shown that insecurely attached children (i.e. characterized by experiences with inconsistent parental responses rather than experiences with consistent parental responses to attachment bids; Bowlby, 1969) are more prone to experience increased and prolonged influence of stress hormones (Radobuljac & Shmueli-Goetz, 2015); secure T1D children show higher level of quality of life than insecure ones, and secure males show lower level of diabetes control than secure females (Costa-Cordella et al, 2020a); child and maternal reflective functioning are higher in the dyad with good diabetes control than in these with poor diabetes control and are negatively correlated with levels of glycated hemoglobin (Costa-Cordella et al, 2020b); individuals with dismissing attachment show worse diabetes outcomes rather than secure and insecure preoccupied ones (Ciechanowski et al, 2004); maternal perceptions of more secure adolescents' attachment are associated with better glycemic control (Rosenberg & Shields, 2009); infants with diabetes-specific autoantibodies are more likely to have insecurely attached mothers (Sepa et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…According to this, diabetes studies have shown that insecurely attached children (i.e. characterized by experiences with inconsistent parental responses rather than experiences with consistent parental responses to attachment bids; Bowlby, 1969) are more prone to experience increased and prolonged influence of stress hormones (Radobuljac & Shmueli-Goetz, 2015); secure T1D children show higher level of quality of life than insecure ones, and secure males show lower level of diabetes control than secure females (Costa-Cordella et al, 2020a); child and maternal reflective functioning are higher in the dyad with good diabetes control than in these with poor diabetes control and are negatively correlated with levels of glycated hemoglobin (Costa-Cordella et al, 2020b); individuals with dismissing attachment show worse diabetes outcomes rather than secure and insecure preoccupied ones (Ciechanowski et al, 2004); maternal perceptions of more secure adolescents' attachment are associated with better glycemic control (Rosenberg & Shields, 2009); infants with diabetes-specific autoantibodies are more likely to have insecurely attached mothers (Sepa et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the present article makes a significant contribution to the realm of psychological support and intervention of patients with such a chronic condition. As regards the relevance of alexithymic traits in persons with diabetes, recent studies have highlighted that mentalization-based interventions can increase diabetes outcomes and promote psychological well-being, especially in adolescents with type 1 diabetes (Iole Colombini and Schivalocchi, 2013 ; Thomakos et al, 2019 ; Costa-Cordella et al, 2020 ). To address alexithymia, the difficulty in identifying and describing emotions, the understanding of defense mechanisms preventing the patient from acknowledging his emotional world is of primary relevance.…”
Section: Discussionmentioning
confidence: 99%
“…It will also potentially affect glycaemic control via consistent emotion regulation allowing for adoption of new health behaviours such as glucose testing and insulin management. This last possibility has already been investigated by Costa-Cordella and colleagues who studied the influence of mentalisation in mother's and their son's between age 8 to 12 and found that a mother's mentalising capability was strongly associated with their child's glycaemic control (Costa-Cordella et al, 2020a).…”
Section: Family Functioning and Outcomes In T1d: Is Attachment Theory A Unifying Factor?mentioning
confidence: 94%